2009
DOI: 10.1007/s10620-009-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and the Myenteric Plexus in Intestinal Ischemia/Reperfusion Injury

Abstract: Ketamine was able to diminish alterations induced by I/R. Myenteric plexus ablation with BAC treatment alone had no effects on intestinal I/R injury. However, this procedure abolished ketamine's protective effects. Ketamine seems to require an intact enteric nervous system to exert its protective action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Such change has been hypothesized to be, at least in part, at the basis of development of visceral hypersensitivity during colonic inflammation. As concerns the intestinal ischemic/reperfusion injury, recent reports have demonstrated that NMDA glutamatergic pathways are involved in the functional changes underlying gastrointestinal dismotility in these conditions 18,49,50 . In the guinea pig ileum, one of the functional consequences of the potentiation of the glutamatergic transmission after glucose/oxygen deprivation is represented by an anomalous increase in the overflow of acetylcholine 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Such change has been hypothesized to be, at least in part, at the basis of development of visceral hypersensitivity during colonic inflammation. As concerns the intestinal ischemic/reperfusion injury, recent reports have demonstrated that NMDA glutamatergic pathways are involved in the functional changes underlying gastrointestinal dismotility in these conditions 18,49,50 . In the guinea pig ileum, one of the functional consequences of the potentiation of the glutamatergic transmission after glucose/oxygen deprivation is represented by an anomalous increase in the overflow of acetylcholine 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, D-lactate was not elevated in the hyperacute phase of intestinal ischemia (1 hour of reperfusion). The specific roles of other markers, such as iFABP, coagulation parameters (41), oxidative stress (42), and adhesion molecules (40), requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a single dose of 50 mg/kg ketamine was administered intraperitoneally to this group after the termination of priapism and the application of constriction bands. [ 8 ] At the end of the experiment, penectomy was performed for histopathological examination, and blood samples were collected from the inferior vena cava for biochemical analysis. After all procedures were completed, rats were euthanized by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%